Flavonoids from the Rhizomes of Kaempferia Parviflora Wall. Ex Baker - Loan, Ly Tu; Hue, Phan Thi Ai; Thanh, Ma Chi (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 4DO - 10.25073/2588-1140/vnunst.5619, 2023)
Kaempferia parviflora Wall. ex Baker, Zingiberaeceae has been used in traditional medicine in Vietnam for the treatment of inflammation, abdominal pain, indigestion, menstrual cramps, fatigue. From the n -hexane fraction of the rhizomes of Kaempferia parviflora , six compounds were isolated and determined as 5-hydroxy-3,7-dimethoxyflavone ( 1 ), 5,7-dimethoxy chrysin ( 2 ), 5-hydroxy-7-methoxyflavone ( 3 ), 5-hydroxy-3,4',7-trimethoxyflavone ( 4 ), 4',5,7-trimethoxyflavone ( 5 ), and 3,4',5,7-tetramethoxyflavone ( 6 ). The structures of 1-6 were elucidated by extensive spectroscopic methods (MS, 1D, and 2D NMR)